Myricetin Attenuated Diabetes-Associated Kidney Injuries and Dysfunction via Regulating Nuclear Factor (Erythroid Derived 2)-Like 2 and Nuclear Factor-κB Signaling - Yang, Zi-Jun; Wang, Hong-Ru; Wang, Yu-Iin; Zhai, Zi-Han; Wang, Liu-Wei; Li, Liang; Zhang, Cheng; Tang, Lin (Frontiers in Pharmacology, 2019)
Background/Aims: Previous studies have suggested that myricetin (Myr) could promote the expression and nuclear translocation of nuclear factor (erythroid-derived 2)-like (Nrf2). This study aimed to investigate whether Myr could attenuate diabetic nephropathy (DN) in wild-type (WT) and Nrf2 knockdown (Nrf2-KD) mice. Methods: Lentivirus-mediated Nrf2-KD and WT mice were used to establish type 1 diabetes mellitus by streptozotocin injection. WT and Nrf2-KD mice were then randomly allocated into 4 groups: control, Myr, DN, and DN+Myr. Myr (100 mg/kg/day) or vehicle was administered for 6 months. Kidneys were harvested and weighed at the end of the experiment. Hematoxylin and eosin staining and Masson’s trichrome staining were used to assess the morphology and fibrosis of the kidneys, respectively. Urinary albumin to creatinine ratio was used to test renal function. Western blotting was performed to determinate oxidative stress or inflammation associated signaling pathways. RT-PCR was performed to detect the expression of fibrosis or inflammatory cytokines at the mRNA level. Results: In WT mice, Myr alleviated diabetes-induced renal dysfunction, fibrosis, and oxidative damage and enhanced the expression of Nrf2 and its downstream genes. After knockdown of Nrf2, Myr treatment partially but significantly mitigated diabetes-induced renal dysfunction and fibrosis, which might be associated with inhibition of the IκB/NF-κB (P65) signaling pathway. Conclusions: This study showed that Myr prevented DN-associated enhanced expression of Nrf2 and inhibition of the IκB/NF-κB (P65) signaling pathway. Moreover, inhibition of IκB/NF-κB (P65) signaling pathway is independent of the regulation of Nrf2. Thus, Myr possessed dual effects that prevented the development and progression of DN, and could be a potential treatment.